Multi-Variant E-Commerce User Interfaces for Business Sustainability - Adam Wasilewski; Anna Zgrzywa-Ziemak (Operations Research and Decisions)
Consumers and their consumption-patterns play an important role in efforts to make businesses and industries more sustainable. Although, theoretical basis for business to engage customers in more sustainable consumption is still under development, data-driven personalizing in e-commerce is emerging as a potential means of supporting company's efforts. However, such analyses are lacking in the literature. The purpose of the article is to adapt the general framework that enables the delivery of multi-variant e-commerce user interfaces to shape customer engagement for sustainability. The framework has been adapted so that it can be used to shape customer engagement for sustainability, using concepts of customer engagement and business sustainability embedded in stakeholder theory. The paper has a practical contribution (empirical verification of the effectiveness of the concept) and a consequent theoretical contribution (development of a sustainability-oriented version of the framework). (original abstract)